Pitfalls on our "New Royal Road": Commentary on Paper by Joyce Slochower. Issue 3 (4th May 2017) - Berman, Emanuel
Abstract : In discussing Joyce Slochower's paper "Going Too Far: Relational Heroines and Relational Excess, " (this issue) the author welcomes its self-critical emphasis, suggesting that analysts from all schools of thought benefit more from noticing the risks and pitfalls in their own approach—thus becoming able to improve their own clinical work—than from polemically highlighting what is faulty in other, competing approaches. Such polemics run a risk of their own: turning our theoretical homes into theoretical fortresses, and blocking richer communication among analysts. He shares the concern about some specific attributes of relational and intersubjective clinical work but relates many of the issues raised by Slochower to tensions and dilemmas present in older models of the analytic relationship as well, offering examples from the work of Freud, Ferenczi, Balint, Winnicott, and Racker.